Gambaran Pengetahuan dan Persepsi Agama terhadap Kesehatan Mental pada Siswa SD Negeri Meruya Selatan 03 pada Tahun 2024 - Ahda Dzikir Aziz; Agam Athilla Alauddin; Aqil Fachrezi Paputungan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
In adolescence there are many biological, psychological, and social changes. But generally the process of physical maturation occurs faster than the process of psychological maturation, Mental health or a good soul is the condition of our inner being in a state of peace and calm, Muslim thinker, Al-Ghazali, believes humans as physical-spiritual beings and the ruhiyah aspect is a real essence. Related to efforts to create peace of mind, making the Al-Qur’an as a representation. This study was conducted to determine the description of knowledge and perceptions of religion towards mental health in students. The research design used was cross-sectional. data collection using a questionnaire method distributed via google from and population Respondents of this study were students of class IV A and B at SDN Meruya Selatan 03. The sampling technique in this study was total sampling with a total of 57 respondents. The results of univariate analysis can be concluded that the majority of 86% of students already know about Mental Health, then the majority of 100% the role of religion is very important for Mental Health. Knowledge about the mental health of adolescent students can be influenced by the information received, this is where the important role of health workers and educational institutions in increasing knowledge about mental health cannot be underestimated. In conclusion, most respondents already have knowledge about mental health according to Islamic teachings and most respondents believe that a lack of understanding of Islam can have a negative impact on mental health stability.